A arte como a glória de qualquer um no museu do mundo e a gravidade do silêncio - Sá, Rubens Pileggi (2016)
From a historical problem that dates back, in Brazilian art, the Concretism and the Neoconcretismo, I develop, since 1998, an artistic trajectory that uses the street like one laboratory of actions, manifestations and artistic interventions. My work is embodied in the relationship between the "expanded field of art" with the body, object and space. It turns out that during of the development of the thesis, I notice an obvious limits of this type of production to of the dissolution of the artistic field, increasingly subsumed by the sociological discourse, making it a sort of commodity to be traded as resistance art. The problem moves then to an investigation of appropriations that can be made that field - place without place - to incorporate them and transform them, at its base, so that art can still be produced once. And if, at first, the statement of a relationship between art and life becomes a militant way, programmatic and pragmatic, in a next moment requires a reflexive deepening method and language. The solution I found, caused by the tension of the current political moment, was to turn my attention to work betting on negativity, in exploring the dimension of emptiness and silence, thinking the lack as a possibility to add an idea, through the viewer's imagination. The practical result is the creation of a glass box, designed to fill the space of a door by means of resonance sound effect and vibration speakers, revealing a small continuous motion. My intention with this is to suggest a situation of instability and the imminence of a possible tragedy, condensing the premises of the field expanded into the critique of institutional debate.